A Potential Mechanism for Targeting Aggregates With Proteasomes and Disaggregases in Liquid Droplets - Mee Hayes, Emma; Sirvio, Liina; Ye, Yu (Frontiers in Aging Neuroscience, 2022)
Insoluble protein deposits are hallmarks of neurodegenerative disorders and common dementia. The aberrant aggregation of misfolded proteins involves a complex cascade of events that occur over time, from the cellular to the clinical phase of neurodegeneration. Declining neuronal health through e.g. increased cell stress and loss of protein homeostasis (proteostasis) functions correlate with the accumulation of aggregates. On the cellular level, increasing evidence support that misfolded proteins may undergo liquid-liquid phase separation (LLPS), which is emerging as an important process to drive protein aggregation. In contrast, the reverse process of aggregate disassembly and degradation has only recently gained momentum, following growing reports of enzymes with distinct aggregate-disassembly activities. In this review, we will discuss the how the ubiquitin-proteasome system, the HSP70 and VCP disaggregation machineries may disassemble and/or degrade endogenous protein aggregates. In addition to their canonically associated functions, these enzymes appear to share a common feature: reversibly assembling into liquid droplets in an LLPS-driven manner. We review the role of LLPS in enhancing the disassembly of aggregates through locally increasing the concentration of these enzymes and co-proteins together within droplet structures. We propose that such activity may be achieved through the concerted actions of disaggregase machineries, the ubiquitin-proteasome system and their co-proteins condensed within transient aggregate-associated droplets (TAADs), ultimately resulting in aggregate clearance. We speculate that sustained engagement of these enzymatic activities within the TAADs will be detrimental to normal cellular functions, where these activities are required. The possibility of facilitating endogenous disaggregation and degradation activities within TAADs and to prevent their prolonged formation potentially represents novel features for therapeutic engagement to accelerate aggregate removal and restore protein homeostasis during the early stages of neurodegeneration.